ANALISIS UPAYA-UPAYA PENGRAJIN TENUN SONGKET DALAM MEMPERTAHANKAN KELANGSUNGAN USAHA DI DESA SUDI MAMPIR KECAMATAN INDRALAYA KABUPATEN OGAN ILIR - Sri Artati Waluyati; Kurnisar; Sulkipani (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2016)
The research titled Analysis Efforts Artisans Weaving Songket In Maintaining Business Continuity In the village Sudimampir Indralaya Ogan Ilir subdistrict. The aim after doing this study is to determine what efforts are being made by the songket weavers in the village Sudimampir in maintaining business continuity. The benefits of research that songket weaving craftsmen doing various strategic efforts to improve the quantity and quality of weaving songket. This study used a qualitative descriptive approach. The population in this study is the songket weavers in the village Sudimampir total of 120 artisans, samples taken as many as 25% of the population that is numbered 30 craftsmen. The technique of collecting data using interviews and observation. From the results of research through interviews stated that efforts songket weaving a going concern by: 1) improving the production quality of weaving songket, 2) The craftsmen manage their finances through loans and also profits. 3) Custom songket reduce expenses that are not so needed and more priority to produce the goods ordered especially goods orders already given an advance, for the wages according to job workers. 6) Varying color of thread and the type of thread used for weaving, woven songket motifs goods on display usually craftsmen produce only a few fruits and function only as examples of goods. 4) Provide the offer price is lower but still did not lose money. 5) Reduce the employees so that it can continue to provide so no appeal to buyers. 7) Following the training of weaving songket held by the government. 8) They have any other skills besides typical Palembang songket weaving. 9) Want to maintain the cultural heritage of Palembang that persisted into the typical Palembang songket weaving.